Coronary Artery Bypass Grafting (CABG) without General Anaesthesia - An Initial Experience in NICVD, Dhaka, Bangladesh - Haque, Md Naimul; Hossain, Md Shahadat; Ferdous, Shahnaz; Beg, Abdul Kaleque; Ahsan, NA Kamrul; Chowdhury, AYF Elahi (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: our initial experience with 15 patients operated on without general anesthesia is reviewed to explore the validity of our surgical strategy. Material and Methods: 15 males between 45-65 years underwent off-pump coronary artery bypass grafting (OPCAB) with high thoracic epidural anesthesia (HTEA) between April to September 2006. Target vessels involved were the single vessel in 5, double vessel in 7 and triple vessel disease in 3 patients. CABG was performed through a median sternotomy in 13 patients and through limited access in 2 patients. Results: Among 15 patients, patients remain awake or were lightly sedated breathing spontaneously in 9 cases. In 3 patients pneumothorax was observed during surgical intervention. Average length of ICU stay was 1 day (range 1 to 2 days). In all cases, patients showed lack of treatable cardiac dysrhythmias and stable haemodynamic response to surgical procedures including cardiac positioning and direct handling. Conclusion: CABG under epidural anesthesia appeared to be safe for and satisfying to the patients. Stable haemodynamics, low incidence of cardiac dysrhythmias and early recovery and discharge from ICU and low cost involvement are among the benefits that can be derived from this technique at least in selected patients. High thoracic epidural anaesthesia was proved to be very efficient in achieving, somatosensory & motor block in the chest, which inturn facilitating CABG without endotracheal general anaesthesia in selected patients. CABG in an awake patient without endotracheal general anaesthesia was first performed in October 1998 with high thoracic epidural block1. Since then, similar cases had been reported in the literature to decrease the invasiveness of the CABG procedure. This report presents our initial experience in 15 patients which was performed during a time period of 6 months. DOI: 10.3329/jbcps.v27i1.4239 J Bangladesh Coll Phys Surg 2009; 27: 22-24